2017
DOI: 10.1016/j.buildenv.2017.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Green façades and in situ measurements of outdoor building thermal behaviour

Abstract: Using green façades in large cities with hot climates has been introduced in the search for more sustainable solutions for urban development. This paper presents the data collected in situ and quantifies the thermal external behaviour of a green wall and a bare one in the same surrounding environment in the city centre of Madrid, Spain. The methodological approach helps to assess the impacts of both walls on the variation of the urban temperature range at the microclimate scale in accordance with environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The studies ranging from observational studies to modelling simulations suggest that the immediate air temperature modifications of vertical greening including direct, indirect, or living wall approaches to range between 0 and 3 K at most, while the effective range seldom exceeds 1 m from the wall surface [e.g. 8, [11][12][13][14][15][16]. Higher performance has been demonstrated when conditions are drier and warmer (summer), relative to colder (autumn and winter) conditions [e.g.…”
Section: Thermalmentioning
confidence: 99%
“…The studies ranging from observational studies to modelling simulations suggest that the immediate air temperature modifications of vertical greening including direct, indirect, or living wall approaches to range between 0 and 3 K at most, while the effective range seldom exceeds 1 m from the wall surface [e.g. 8, [11][12][13][14][15][16]. Higher performance has been demonstrated when conditions are drier and warmer (summer), relative to colder (autumn and winter) conditions [e.g.…”
Section: Thermalmentioning
confidence: 99%
“…Vertical greening, also referred to as green wall or facade greening, is likewise helping cities adapt to climate change by reducing air and facade surface temperatures and peak energy demand (Cheng et al 2010;De Jesus et al 2017;Kalani et al 2016). However, location, placement, and plant configuration determine their effectiveness in terms of surface and air temperature reduction and energy saving.…”
Section: Performance Of Urban Greenery In Mitigating Urban Heat Islanmentioning
confidence: 99%
“…Perini et al found that the average temperature of the air cavity, inner leaf, and 0.1 m in front of a GF was reduced by 0.34 • C, 0.17 • C, and 0.13 • C, respectively, compared to the point in front of a bare wall, and there was no difference found at a distance higher than 1.0 m in front of the GF [17]. De Jesus et al investigated two LWSs in situ and found a maximum outdoor temperature difference of 1.5 • C compared at distances of 0.5 and 4.5 m [3]. Koyama et al showed that room temperature was reduced by 0.15 • C and 4.0 • C due to transpiration and shading cooling effects, respectively [18].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the lack of land in some densely built-up areas, the vertical green strategy has been introduced to provide more green space and dissipate the thermal stress under the extreme artificial environment. As one of the vertical greenery systems (VGSs), the application of green walls (GWs) has the potential to optimize the energy consumption of buildings [2] and increase outdoor thermal comfort [3].…”
Section: Introductionmentioning
confidence: 99%